2004
DOI: 10.1021/jo0492618
|View full text |Cite
|
Sign up to set email alerts
|

Pd-Catalyzed Cross-Coupling of Baylis−Hillman Acetate Adducts with Bis(pinacolato)diboron:  An Efficient Route to Functionalized Allyl Borates

Abstract: The cross-coupling of Baylis-Hillman acetate adducts and bis(pinacolato)diboron proceeds readily in high yields in the presence of palladium catalyst to produce 3-substituted-2-alkoxycarbonyl allylboronates. These allylboronates can be transformed to stable allyl trifluoroborate salts by addition of excess aqueous KHF2. Both the allylboronate and allyltrifluoroborate derivatives react with aldehydes to afford functionalized homoallylic alcohols stereoselectively.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
37
0

Year Published

2006
2006
2010
2010

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 70 publications
(37 citation statements)
references
References 44 publications
(21 reference statements)
0
37
0
Order By: Relevance
“…[10][11][12] On the other hand, allylboronates are remarkably air-and moisturestable in solution, which allows their in situ application in various multi-step one-pot reactions. [6][7][8][13][14][15][16][17][18][19][20][21][22] In previous studies, we have shown [6][7][8] that allylboronates generated in situ from allylic alcohols (such as 1a-f), acetates (such as 1g, h) and other precursors (such as 1i) by palladium-catalyzed processes readily react with aldehyde, acetal, ketone and imine substrates in a one-pot sequence.…”
Section: Introductionmentioning
confidence: 99%
“…[10][11][12] On the other hand, allylboronates are remarkably air-and moisturestable in solution, which allows their in situ application in various multi-step one-pot reactions. [6][7][8][13][14][15][16][17][18][19][20][21][22] In previous studies, we have shown [6][7][8] that allylboronates generated in situ from allylic alcohols (such as 1a-f), acetates (such as 1g, h) and other precursors (such as 1i) by palladium-catalyzed processes readily react with aldehyde, acetal, ketone and imine substrates in a one-pot sequence.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, it was shown that allyltrifluoroborates, readily obtained from Baylis-Hillman acetates via palladium-catalyzed reactions, reacted with aldehydes to give the corresponding homoallylic alcohols in high yields and diastereoselectivities. 96 A strategy for the synthesis of phosphatase inhibitors TMC-69-6H and analogues involved diastereoselective crotylation under biphasic conditions (Scheme 66). 122 Indeed, reaction of potassium (E)-crotyltrifluoroborate with aldehyde 17 led to formation of the antihomocrotyl alcohol product in 96% yield and dr > 95%.…”
Section: Diastereoselective Allylation Reactions Of Aldehydesmentioning
confidence: 99%
“…[4] S N 2' [5,6] or p-allyl- [7] type reactions have also been described on Baylis-Hillman adducts, but the allyl alcohol moiety had to be further transformed to carbonate or acetate, which are better leaving groups. For example, Kabalka et al reported palladium-catalyzed cross-coupling reactions of Baylis-Hillman acetates with bis(pinacolato)diboron [8] or potassium trifluoroA C H T U N G T R E N N U N G (organo)borates, [9] allowing the formation of stereodefined alkenes via p-allylpalladium intermediates. [10] In terms of atom economy, [11] the use of unactivated Baylis-Hillman adducts, would be more desirable but they are generally less reactive in transition metal catalyzed reactions.…”
Section: Introductionmentioning
confidence: 99%